-52 and -54
Step-by-step explanation
Step 1
Let
x represents a number,
x+2, represents the even number after x
then
x and x+2 are two consecutive integers
Step 2
the sum is -106,then
![\begin{gathered} x+(x+2)=-106 \\ x+x+2=-106 \\ 2x+2=-106 \\ \text{subtract 2 in both sides} \\ 2x+2-2=-106-2 \\ 2x=-108 \\ \text{divide both sides by 2} \\ (2x)/(2)=(-108)/(2) \\ x=-54 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/80gei3kme963fr0igilqnx2bqoh7ostsvy.png)
Step 3
a number is -54
the next number is -54+2=-52
Hence, the numbers are -52 and -54.
I hope this helps you